NARRACIÓN DEPORTIVA RADIAL Y SU RELACIÓN CON EL CRITERIO DE LOS AFICIONADOS - Guerrero Muzo, Elian Alexander (2022)
The present research is focused on the study of the Communication Language and Journalistic Styles, in order to define the impact that communication generates in a certain group of society. Its main objective is to determine the existing relationship between sports narration and the criteria of the fans, it was taken into account to establish the indicators of perception to achieve an analysis on the relationship of the variables; in such case in its methodology an explanatory research scope was used, where its research techniques were exploratory-comparative and field where information was obtained on the relationship that currently exists between radio media and the fans, in this way it was possible to determine what shortcomings exist in the subject of study. In addition, the quantitative method was developed to obtain the results in which surveys were developed based on a questionnaire with a bank of 8 questions addressed to the fans to determine the degree of acceptance in the activities of radio sports narration and it is concluded that it is of utmost importance to make a proposal for a guide of good practices of radio sports narration, in order to establish quality standards at the level of sports journalism and to determine that a guide should be developed to help improve the professional level of journalists and thus increase the satisfaction of the fans.